TANTANGAN PERPUSTAKAAN DAN ARSIP UNTUK MEMILIH METODE MASS DEASIFIKASI SEBAGAI SALAH SATU UPAYA PELESTARIAN DALAM MENYELAMATKAN BAHAN PERPUSTAKAAN DARI KEHANCURAN - Made Ayu Wirayati (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
Paper fragility has always been aproblem for libraries and archives. Along with the development of science, efforts have been done in order to preserve paper-based materials in libraries. One of certain ways in preserving such materials is by reducing the acid level of paper known as deacidification. Deacidifcation process is done by combining certain chemicals which is the applied to paper through sprays or submersion. The method can be carried outfor separated sheets or pages or bulk documents without having to detach pages from  binding. The latter is known as mass deacidifcation. By conducting a mass eacidifcation, attempts to save  library materials can be done comprehensively to allow the materials to bepreserved for the next  1OO or 500 years.